2022
DOI: 10.1155/2022/7812099
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Protects against Renal Ischemia-Reperfusion Injury by Regulating Th17/Treg Cell Immune Balance

Abstract: Inflammation is a critical mediator of renal ischemia-reperfusion (I/R) injury (IRI), and T lymphocytes exert a key role in the renal IRI-induced inflammation. Connexin 43 (Cx43) is related to the maintenance of T lymphocyte homeostasis. Various preclinical researches have reported that estrogen is a renoprotective agent based on its anti-inflammatory potential. The present research is aimed at studying the role of T lymphocytes activated by Cx43 in 17β-estradiol-mediated protection against renal IRI. Female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We showed that these hormones have nephroprotective effects in the case of female rats and predominantly negative effects in male rats ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). Previously, it was demonstrated that a single administration of exogenous estradiol resulted in a significant reduction in pyroptosis-associated inflammation in the damaged kidney of non-ovariectomized females [ 26 ] and reduced the severity of renal injury in ovariectomized females [ 27 , 28 , 29 ]. Regarding progesterone, it has been shown that the administration of this hormone to ovariectomized female rats protected against glomerulosclerosis, decreased profibrotic factors, and eliminated other manifestations of nephropathy in a model of diabetes-associated kidney damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that these hormones have nephroprotective effects in the case of female rats and predominantly negative effects in male rats ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). Previously, it was demonstrated that a single administration of exogenous estradiol resulted in a significant reduction in pyroptosis-associated inflammation in the damaged kidney of non-ovariectomized females [ 26 ] and reduced the severity of renal injury in ovariectomized females [ 27 , 28 , 29 ]. Regarding progesterone, it has been shown that the administration of this hormone to ovariectomized female rats protected against glomerulosclerosis, decreased profibrotic factors, and eliminated other manifestations of nephropathy in a model of diabetes-associated kidney damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These properties provide significant protective benefits to females, particularly in conditions that pose stress to the kidneys. Estrogen's ability to modulate various cellular pathways, such as TGF-βRI expression, modulation of Th17/Treg cell balance and Cx43 expression which further reduce renal ischemia-reperfusion injury contributes to its protective role [15][16][17] , which is more pronounced in females due to higher circulating levels of E2 compared to males. Also, during high temperature or heat stress conditions, females may receive enhanced renal protection due to the synergistic effects of E2 and heat shock protein (HSP) induction 33 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sex-based physiological differences significantly influence the body's response to environmental stressors, including heat stress. Males and females exhibit distinct hormonal profiles, body compositions, and thermoregulatory mechanisms, resulting in varied susceptibility to heat stress and its subsequent impact on kidney function [15][16][17] . Recognizing these differences is essential for developing effective prevention and intervention strategies.…”
mentioning
confidence: 99%
“…Then the results of flow cytometry showed that Th17 cells in both blood and spleen were up-regulated in renal I/R injury mice which were then reversed by AT, and Treg cells were opposite with Th17 cells. Previous study found that Treg cell was not only present in the blood and spleen, they also infiltrate the kidney tissue after renal ischemia-reperfusion [ 33 ]. The effect of AT on Treg cells was mainly through directly increasing the number of Treg cells in the kidney tissue or promoting the transfer of cells outside the kidney to the kidney tissue, which remained to be discussed.…”
Section: Discussionmentioning
confidence: 99%